Biology and utilization of the mudskipper pseudapocryptes elongatus in the Mekong River Delta, with aspects on other mudskippers in the area - Bucholtz, Rikke Hagstrom (University of Aarhus, 2005)
The thesis consists of a general introduction, four separate papers concerning biology and utilization of the mudskipper pseudapocryptes elongatus and finally conclusions and recommendations for future management and research.